PENERJEMAHAN TEKS SASTRA DAN BUDAYA - Wijaya, Iriany Kesuma (JURNAL TARBAWIYAH, 2015)
Translation is the process of transferring a message from the source language into the target language by considering the range of matching and text. In the transfer of messages, a translator must master the source language and the various texts to be translated. McGuire stated that "the translator Should have a perfect knowledge of Both source language and target language". Powered by Brislin that "the translator Should know Both the source and receptor languages, Should Be familiar with the subject matter, and Should have facility of expression in the receptor language."Related to culture in translation Leonardi argues that the translator was faced with two languages and two cultures simultaneously, namely the language of culture and cultural sources of the target language. Culture is a culture that involves all the elements contained in these two languages the user community, namely the name, history, religion, beliefs, traditions, customs, clothing, social structure, daily life - days, social relations, food and language ".